Cover plants with potential use for crop-livestock integrated systems in the Cerrado region - Arminda Moreira de Carvalho (Pesquisa Agropecuária Brasileira, 2011)
The objective of this work was to evaluate the effects of lignin, hemicellulose, and cellulose concentrations in the decomposition process of cover plant residues with potential use in no-tillage with corn, for crop-livestock integrated system, in the Cerrado region. The experiment was carried out at Embrapa Cerrados, in Planaltina, DF, Brazil in a split plot experimental design. The plots were represented by the plant species and the subplots by harvesting times, with three replicates. The cover plants Urochloa ruziziensis, Canavalia brasiliensis, Cajanus cajan, Pennisetum glaucum, Mucuna aterrima, Raphanus sativus, Sorghum bicolor were evaluated together with spontaneous plants in the fallow. Cover plants with lower lignin concentrations and, consequently, higher residue decomposition such as C. brasiliensis and U. ruziziensis promoted higher corn yield. High concentrations of lignin inhibit plant residue decomposition and this is favorable for the soil cover. Lower concentrations of lignin result in accelerated plant decomposition, more efficient nutrient cycling, and higher corn yield.